''Sorry mate, you're finishing tonight'': a historical perspective on employment flexibility in the UK film industry. (1st July 2014) - ,; ,
Abstract : This article considers the nature of employment in the UK Film Industry in the period 1927––1947 against a background of US domination of the global market for film. Drawing on archived interview material from 60 participants in the archive of the History Project of BECTU (the British trade union for Media and Entertainment workers) the article focusses on entry routes, working hours, training and pay grades to assess the degree of stability present in the labour market across a number of selected below-the-line film production occupations. This provides an historical context to debates surrounding the organisation of work in the sector, which is characterised by both continuity and change. The article argues that the UK film industry has never been a stable, ''job-for-life'' sector, nor have its labour processes ever followed mass production lines. It supports assertions that assumptions of linear development from secure to casualised employment are inadequate for understanding work in this sector.